Cultivating the gems within special population: using pathopysiological insight to guide server and smarter antimicrobial dosing in women - Jamluddin, Nurul Ashikin; Jamal, Janattul Ain (Faculty of Pharmacy, 2025)
Women bear a disproportionate burden of infectious diseases requiring antimicrobial treatment, ranging from urinary tract infections (UTIs) to obstetric and reproductive tract infections. Although antimicrobial therapy is typically guided by standardized dosing regimens and population-based data, one crucial consideration is often overlooked, women are not smaller versions of men. The differences in anatomy, physiology and hormonal profiles can significantly influence how women experience infections, respond to antibiotics, and develop complications from resistant pathogens. These variations are largely driven by alterations in pharmacokinetics (PK) resulting from unique pathophysiologic changes,such as pregnant women. This suggests that fixed, “one-size-fits-all” antibiotic regimens may not be optimal for women. The concern becomes even more pressing in the era of emerging resistant, compounded by limited local access to and/or availability of certain antimicrobials.